Luz, câmera na educação: o cinema educativo e a renovação da cultura material escolar e da educação em Caxias do Sul - RS (1947-1960) - Dewes, Elisângela Cândido da Silva (My University, 2025)
This thesis is linked to the line of research History and Philosophy of Education of the Graduate Program in Education of the University of Caxias do Sul and aims at studying Educational Cinema in Rio Grande do Sul, particularly in the city of Caxias do Sul, to analyze and understand the use of this material as a resource for the renewal of education and a given school culture. The time frame covers the period from 1947 to 1960, which alludes to the performance of Professor Ester Troian Benvenutti at the Board of Municipal Public Instruction and as a Teaching Advisor in the city. Methodologically, it is based on Oral History and Historical Documentary Analysis, with the contribution of documents and the narrative of the memories of subjects who lived the experience of cinema in an educational context, realizing the probable consequences of this use on schooling and daily practices. In this sense, different sources were mobilized, such as: newspapers of national, state and regional circulation; bulletins, newspapers and magazines of the pedagogical press; legislation; documents of the Municipal Public Administration and the Board of Public Instruction; Teaching programs; Correspondence; photographs; documents of Murialdo Rural Teacher Training (Normal) School; audiovisual documents; transcripts of interviews carried out by other local researchers. As a subsidy for Oral History, the narratives of subjects (students, teachers, practitioners or members of community that were touched by film actions), based on semi-structured interviews transcribed and analyzed as documentary sources. The study is developed from the perspective of Cultural History in dialogue with the History of Education, based on concepts such as: strategies, tactics, school culture, school material culture, representation and practices. To this end, it is supported by Certeau (1990), (1994); Chartier (1990), (1991); Escolano Benito (1995), (2017), (2018) and Souza (2007), (2013). From the procedure of analyzing the documents and memories of the interviewed subjects, themes emerge that are organized into categories, prioritizing the following for the construction of the analyzes: Educational Cinema - National / Regional and Municipal Context; Educational Cinema - Community; Educational Cinema - Material Culture; Educational Cinema - Uses and Contents; Educational Cinema - Church. The study proposed reflections on the contexts that permeated the insertion of cinema in the country; the transit of ideas about pedagogical renewal and school material culture; as well as on the dialogues at the national, state and municipal levels that reverberated to the use of cinema as a school and out-of-school educational support. In this scenario, the thesis defended is that cinema was a material of school culture, between 1947 and 1960, in Caxias do Sul, based on the conceptions of renewal of pedagogical practices that aimed at a reconfiguration of the society of the time, being also used as a resource to control the flow of trends outside the school space, and about a given local culture. Evidence emerged from the study that the educational practices that included the use of cinema, in the city of Caxias do Sul, were aligned with what was carried out in other regions of the country, and that they were oriented as resources for renewal, by institutions that assumed a given organization of the educational field, in a public, private character and from services/entities in dialogue with the government. [resumo fornecido pelo autor]
Esta tese vincula-se à linha de pesquisa História e Filosofia da Educação do Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul e tem como objetivo o estudo do Cinema Educativo no Rio Grande do Sul, particularmente, na cidade de Caxias do Sul, para analisar e compreender o uso desse material como um recurso para a renovação da educação e de uma dada cultura escolar. O recorte temporal compreende o período de 1947 a 1960 que alude a atuação da professora Ester Troian Benvenutti junto à Diretoria da Instrução Pública Municipal e como Orientadora do Ensino na cidade. Metodologicamente tem o aporte da História Oral e da Análise Documental Histórica, com a contribuição de documentos e da narrativa das memórias de sujeitos que viveram a experiência do cinema em um contexto educativo, percebendo os prováveis desdobramentos desse uso sobre a escolarização e para as práticas cotidianas. Nesse sentido, foram mobilizadas diferentes fontes, como: jornais de circulação nacional, estadual e regional; boletins, jornais e revistas da imprensa pedagógica; legislações; documentos da Administração Pública Municipal e da Diretoria da Instrução Pública; Programas de ensino; Correspondências; fotografias; documentos da Escola Normal Rural Murialdo; documentos em audiovisual; transcrições de entrevistas realizadas por outros pesquisadores locais. Como subsídio para a História Oral, as narrativas de sujeitos (alunos, professores, profissionais ou comunidade que foi sensibilizada pelas ações de cinema), a partir de entrevistas semiestruturadas transcritas e analisadas como fontes documentais. O estudo se desenvolve na perspectiva da História Cultural em interlocução com a História da Educação, fundamentado por meio de conceitos, como: estratégias, táticas, cultura escolar, cultura material escolar, representação e práticas. Para tanto, tem o apoio em Certeau (1990), (1994); Chartier (1990), (1991); Escolano Benito (1995), (2017), (2018) e Souza (2007), (2013). Do procedimento de análise dos documentos e das memórias dos sujeitos entrevistados, emergem temas que são organizados em categorias, priorizando-se para a construção das análises as seguintes: Cinema Educativo - Contexto Nacional / Regional e Municipal; Cinema Educativo - Comunidade; Cinema Educativo - Cultura Material; Cinema Educativo - Usos e Conteúdos; Cinema Educativo - Igreja. O estudo propôs reflexões acerca dos contextos que permearam a inserção do cinema no país; do trânsito de ideias sobre a renovação pedagógica e da cultura material escolar; bem como em torno dos diálogos em esferas nacional, estadual e municipal que reverberaram para o uso do cinema como suporte educativo escolar e fora da escola. Nessa conjuntura, a tese defendida é a de que o cinema foi um material da cultura escolar, entre os anos de 1947 e 1960, em Caxias do Sul, tendo como premissa as concepções de renovação das práticas pedagógicas que visavam a uma reconfiguração da sociedade da época, sendo, também, utilizado como um recurso para controle do fluxo de tendências externas ao espaço escolar, e acerca de uma dada cultura local. Do estudo emergiram evidências de que as práticas educativas que compreendiam o uso do cinema, na cidade de Caxias do Sul, estiveram alinhadas ao que se realizava em outras regiões do país, e que eram orientadas como recursos para a renovação, por instituições que assumiam uma dada organização do campo educativo, em caráter público, particular e a partir de serviços/entidades em diálogo com o poder público. [resumo fornecido pelo autor]
Keywords: Educação - História; Educação - Estudo e ensino; Cinema; Escolas rurais - Caxias do Sul (RS); Education - History; Education - Study and teaching; Motion pictures; Rural schools - Caxias do Sul (Brazil)